The effects of land use on environmental features and functional organization of macroinvertebrate communities in Patagonian low order streams - Miserendino, Maria Laura (2010)
Benthic invertebrates, water quality variables, chlorophyll a and particulate organic matter (POM) were studied in 18 sites of mountain streams in Patagonia (Argentina) subjected to six different land uses: native forest, pine plantation, pasture, harvest forest, urban and reference urban. Three streams of each land use were studied in March 2006. Macroinvertebrates were sampled in three riffles and three pools (n = 108) and biomass of detrital fractions of POM were quantified. Overall benthic POM biomass was higher at native and harvest forest than pastures, whereas fine fraction (FPOM) was higher in harvest forest than in pastures. Regarding to autotrophic subsidies bryophytes were the only that changed consistently among uses. These differences in energy resources were correlated with changes in community attributes. Shredder richness was clearly higher at native and harvest forest than exotic pine plantations, collector gatherers density was consistently high at harvest sites, and total density was significantly higher at urban and harvest forest. Multidimensional scaling ordination based on macroinvertebrate density data showed a clear separation of forested (either native or exotic species) from riparian modified areas (pasture, urban and harvest sites). Environmental variables having explanation power on macroinvertebrate assemblages were mostly related with: detritus availability (wood and leaves biomass) and impairment (total phosphorous and % sand). These results confirm that macroinvertebrate assemblage structure in Patagonian low order streams can be altered by land use practices. Among guild structure measures, those indicators based on benthic community functional attributes, shredders richness and collectors density, resulted good candidates to assess land use impacts. On account of riparian corridor management may be critical to the distribution of benthic taxa, the maintenance of good conditions of vegetation adjacent to rivers will enhance water quality and the environment for highly endemic headwater communities of Patagonian streams.